Surface adhesion fermentation: a new fermentation category - Gutiérrez-Correa, Marcel (2003)
Basic knowledge on solid state fermentation and on biofilm formation is summarized and related to cell adhesion processes. These subjects are covered from the engineering and molecular biology points of view. Contrary to the common believe, the advantages of solid state fermentation are related to the adhesion of fungi to solid particles instead of being due to the low water content. Thus, solid state fermentation and biofilm fermentation (erroneously known as adsorption immobilization) are technical variants of the same biological process, and should be referred as Surface Adhesion Fermentation.